FAKTOR PENDUKUNG PEMULIHAN UMKM DI SEKTOR PARIWISATA TERDAMPAK PANDEMI COVID-19 - Manik Pertiwi, AA.; Diah Kesumadewi, Putu (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 1 (2023): Jurnal IPTA (July 2023), 2023)
The Covid-19 pandemic caused many tourism workers to lose their jobs. Tourism workers who have been laid off try to open businesses despite limited capital and human resources through the Micro, Small and Medium Enterprises (MSMEs) sector. During the Covid - 19 pandemic, MSMEs in Cemagi Village, Mengwi District, also felt the impact due to the absence of visiting tourists. This study aims to 1) find out the factors that support the recovery of Micro, Small and Medium Enterprises (MSMEs) in the tourism and creative economy sectors affected by the Covid-19 pandemic in Cemagi Village, Mengwi District, Badung Regency. 2) to find out the most dominant factors which are supporting factors for the recovery of Micro, Small and Medium Enterprises (MSMEs) in the tourism and creative economy sectors affected by the Covid -19 pandemic in Cemagi Village, Mengwi District, Badung Regency. This research used 70 MSME respondents using a saturated sampling technique. Data will be analyzed using quantitative descriptive analysis and using factor analysis. Based on the results of calculations using factor analysis, there are 12 variables grouped into 2 factors, namely digitalization of MSME management and factors of motivation and legal protection for MSMEs which are supporting factors for the recovery of Micro, Small and Medium Enterprises (MSMEs) in the tourism and creative economy sectors that are affected Covid 19 pandemic in Cemagi Village, Mengwi District, Badung Regency. Of these two factors, the digitalization factor of MSME management is the most dominant.